Growth of lettuce (Lactuca sativa L.) affected by cadmium concentrations and toxicity alleviation by calcium supplement - Jibril, Sani Ahmad (2017)
Rapid urbanization and population growth contribute to shortage of fresh water globally. Farmers in many developing countries resort to the utilization of untreated urban wastewater in irrigation. This unconventional waters contains toxic elements from households and industries such as mercury, chromium, lead and cadmium (Cd) that can be toxic to both plants and animals. Lettuce (Lactuca sativa L.) is a good accumulator of these toxic elements, especially Cd in the leaves; and therefore was selected in this research to study the effect of Cd on morphological, physiological, biochemical and anatomical attributes of lettuce.